Ecological validity and reliability of an age-adapted endurance field test in young male soccer players - Castagna, C.; Krustrup, P.; D'Ottavio, S.; Pollastro, C.; Bernardini, A.; Araújo Póvoas, C. S. (The Journal of Strength and Conditioning Research, 2019)
The purpose of this study was to examine the reliability and the association with relevant match activities (ecological validity) of an age-adapted field test for intermittent high-intensity endurance known as Yo-Yo intermittent recovery level 1 children's test (YYIR1C) in young male soccer players. Twenty-eight young male outfield soccer players (age 11.1 ± 0.9 years, height 142 ± 4.4 cm, body mass 37.0 ± 5.9 kg) with at least 2 years of experience in soccer competitions were tested twice using YYIR1C and an age-adapted competitive small-sided game (i.e., 9v9), 7 days apart in a random order. The YYIR1C performance showed an excellent relative (intraclass correlation coefficient = 0.94) and a good absolute reliability (typical error of measurement as percentage of the coefficient of variation = 5.1%). Very large and significant associations were found between YYIR1C performance and match high-intensity activity (r2 = 0.53). Large correlations were found between YYIR1C and match sprinting (r2 = 0.42) and high-intensity metabolic power (r2 = 0.46) distances. Match total distance was largely associated with YYIR1C (r2 = 0.30). The results of this study showed that YYIR1C may be considered a valid and reliable field test for assessing intermittent high-intensity endurance in young male soccer players. Because of the relevance of aerobic fitness in youth soccer, future studies testing the sensitiveness of YYIR1C are necessary.